High Modulus Biodegradable Polyurethanes for Vascular Stents: Evaluation of Accelerated in vitro Degradation and Cell Viability of Degradation Products - Sgarioto, Melissa; Adhikari, Raju; Gunatillake, Pathiraja A.; Moore, Tim; Patterson, John; Nagel, Marie-Danielle; Malherbe, François (Frontiers in Bioengineering and Biotechnology, 2015)
We have recently reported the mechanical properties and hydrolytic degradation behaviour of a series of NovoSorb™ [1] biodegradable polyurethanes (PUs) prepared by varying the hard segment (HS) weight percentage from 60-100. In this study the in-vitro degradation behaviour of the PUs with and without extracellular matrix (ECM) coating was investigated under accelerated hydrolytic degradation (phosphate buffer saline; PBS/70°C) conditions to allow complete degradation. The mass loss at different time intervals and the effect of aqueous degradation products on the viability and growth of Human Umbilical Vein Endothelial Cells (HUVEC) were examined. The results showed that for most PUs in the series the degradation medium turned acidic and the extent of this was dependent on the HS percentage. As the HS decreased, a drop in pH was observed, suggesting that the by-products of soft segment (SS) degradation causing the solution to be acidic. Most of the samples were completely eroded by 18 weeks, except PU containing more than 70% HS which only showed partial degradation with no significant change in appearance. The cytotoxicity tests on HUVEC cells of the aqueous extracts obtained after 18 weeks incubation showed that toxicity was dependent on 3 factors: dose, percentage of HS and degradation time. HUVEC growth is similar to but not identical to that observed with tissue culture polystyrene (TCPS) standard. The results from this in-vitro cytotoxicity study suggest that the mixture of degradation products formed during the accelerated degradation of this PU series are not toxic to cells under the experimental conditions used.